The Educational Value and Emotional Impact on Medical Students After Participating in Transplant Organ Retrieval. (March 2021) - Reed, Alistair J. M.; Baldwin-Smith, Rhiannon; Arwyn-Jones, James; Knight, Simon; Quiroga, Isabel
Introduction: Medical students and healthcare professionals lack knowledge and confidence in organ transplantation which stems in part from a lack of exposure to transplant surgery at medical school. To address this, we developed a program that allowed students to attend organ retrievals and assessed its efficacy as an educational intervention. Methods: Students were invited to attend organ retrievals through a voluntary program. Students then completed an anonymous, self-administered questionnaire (n = 40) designed to capture the perceived educational value and emotive impact of attending an organ retrieval, and its effect on career aspirations. Quantitative and qualitative data were analyzed. Results: 100% of students would recommend attending an organ retrieval to a colleague. Students strongly agreed that attending an organ retrieval was a useful learning experience (87.5%) and 90% of students felt more confident discussing organ donation with patients and relatives. 50% of students were more likely to pursue a career in transplant surgery. Students recognized a number of difficulties associated with the emotive impact of organ procurement. Conclusion: An organ retrieval program for medical students offers a novel learning opportunity, and may increase knowledge and improve attitudes toward transplantation in future healthcare professionals. However, the emotive impact of exposing students to organ retrievals must also be recognized.